Investigations on the macro-meso cumulative damage mechanism of the discontinuities in soft-hard interbedded rock mass under pre-peak cyclic shear loading. (October 2022) - Xu, Bin; Liu, Xinrong; Zhou, Xiaohan; Huang, Junhui; Wang, Linfeng; Lin, Guangyi; Wang, Jiwen; Zhang, Jilu
Abstract: To investigate the macro-meso cumulative damage mechanism of the discontinuities in soft-hard interbedded rock mass, laboratory pre-peak cyclic shear tests and PFC 2D meso numerical calculations under constant normal load (CNL) were carried out, considering the effects of moisture content, normal stress, shear rate, shear amplitude, first-order asperity angle and number of cyclic shear. The curve of the shear stress with shear displacement can be divided into six stages, i.e., initial nonlinear compression-shear deformation, compression-shear deformation of approximate linear elasticity, cyclic shear cumulative damage deformation, compression-shear deformation with slowly rising stress, compression-shear deformation with sharply rising stress and compression-shear deformation of brittle stress drop. The peak (residual) shear strength and cumulative shear (normal) displacement decrease and increase, respectively, with number of cyclic shear increasing under the same moisture content, normal stress, shear rate, shear amplitude or first-order asperity angle; under the same number of cyclic shear, these increase and decrease, respectively, with normal stress or first-order asperity angle increasing, while these decrease and increase, respectively, with moisture content, shear rate or shear amplitude increasing. The curve of the meso cumulative damage crack number (energy) with shear displacement shows the characteristics of a slight increase-steep increase, a slow increase and a steep increase-slow increase-steep increase (crack number) or steep increase-slow increase-steep decrease (energy) in the early, middle and later stages, respectively, while the curve of that with number of cyclic shear shows the characteristics of a steep increase and slow increase in the early and later stages, respectively. The macro experimental observations and meso numerical results are in good agreement, and the typical failure modes of the rock discontinuities were summarized as compaction– crack initiation failure, cyclic dislocation– penetration failure and separation– gnawing failure; meanwhile, the macro-meso cumulative damage cracks are approximately an "inverted U-shaped" and densely distributed near the rock discontinuities.